A New Era of Performance Evaluation - Pieper, S.M.; Paul, J.M.; Schulte, M.J. (Computer (Long Beach, Calif.), 2007)
Long-standing techniques for performance evaluation of computer designs are beginning to fail. Computers increasingly interact with other computers, humans, and the outside world, leading to scenario-oriented computing, an emerging category of design that will enable future consumer devices and usher in a new era of performance evaluation.